Teaching Indonesian for Foreigners Online: Pre-service English Teachers Constraints - Syafryadin, Syafryadin; Santiana, Santiana; Wardhana, Dian Eka Chandra; Guntur, Muhammad (Jurnal Pendidikan Progresif, 2022)
Teaching Indonesian for Foreigners Online: Pre-service English teachers Constraints. Objectives: Thus, the research aimed to know the constraints of teaching Indonesian for foreigners online. Methods: The researcher employed qualitative research. The research sample was  20 pre-service teachers who taught Indonesian for foreigners in online mode. The total foreigners were about twenty.The research used semi-structured interview to gather the data. Then, to analyze the data, several stages were done namely data reduction, data display, and conclusion. Findings: The result showed that in the pre-activity, the teacher did not know how to master the online application. Besides, the teacher was nervous to teach foreigners because the teacher was not usual to teach foreigner with different cultural background. In main activity, the teacher found that students were bored and also lack of Indonesian skill, like grammar, pronunciation and vocabulary. In the post-activity, the teacher did not know how to do online assessment for teaching indonesian. Conclusion: In short, the teachers’ constratins were existed in the teaching Indonesian for foreigners in online mode. This constraints must be anticipated by the teachers.  Keywords: teaching indonesian for foreigners, constratins, online learning.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202201